FAST CBT for pediatric OCD: A multiple-baseline controlled pilot trial of parent training in exposure and response prevention delivered via telehealth - Farrell, Lara J.; Nabinger de Diaz, Natalja A.; Mathieu, Sharna; McKenzie, Matthew L.; Miyamoto, Taka; Donovan, Caroline L.; Waters, Allison M.; March, Sonja; Bothma, Nicole; Kroon, Rianca; Simcock, Gabrielle; Ware, Robert S.; et al. (Frontiers in Psychology, 2022)
Objective: The current study utilised a single case series, non-concurrent multiple baseline design to examine the efficacy of training parents via telehealth videoconferencing in exposure and response prevention (ERP) for home delivery of the treatment for their children and adolescents with obsessive compulsive disorder (OCD). Method: There were nine participants aged 8 to 4 years who had received a primary diagnosis of OCD. The design involved a series of AB replications, whereby following pre-treatment assessments participants were randomly assigned to either a 2-week (n = 4) or 3-week (n = 5) baseline condition with weekly monitoring of their child’s OCD symptoms. Following baseline, parents participated four weekly telehealth parent-training modules in delivering FAST (Families Accessing Skills Training) cognitive behaviour therapy (CBT) with ERP (CBT-ERP) to children with OCD via videoconferencing with the clinician. Primary outcome measures were OCD symptom severity, diagnostic severity, and global functioning, which were assessed post-treatment and at 2 month follow-up. Results: The stability of the baseline period from pre-treatment to week 2 (for the 2-week condition) or to week 3 (for the 3-week condition) was established as there were no significant differences across baseline scores for parent target obsessions or parent target compulsions ratings. Significant improvements on the primary outcomes of clinician assessed symptom severity, diagnostic ratings, and global functioning were observed from baseline to post-treatment, and continued to 2 months follow-up. Conclusions: These data suggest that brief, parent training in FAST CBT-ERP via telehealth provides an overall effective intervention that reduces youth OCD symptom severity and global functioning, particularly for those with mild to moderate severity.